\[ \begin{array} ((A) A\: and \: B \: are\: mutually\: exclusive & (B) P(A′B′) = [1 – P(A)] [1 – P(B)] \\ (C) P(A) = P(B) \quad & (D) P(A) + P(B) = 1 \end{array} \]

- Two events $A$ and $B$ associated with a random experiment are independent if $P(A\cap B)=P(A) P(B)$
- Also If $A$ and $B$ are independent then $A'$ and $B'$ are independent $P(A')=1-P(A)$

Since $A$ and $B$ are independent $A'$ and $B'$ are independent, By definition of independence of events:

$P(A'\cap B')=P(A')P(B')$ =$[1-P(A)][1-P(B)]$

Ask Question

Tag:MathPhyChemBioOther

Take Test

...